2008
DOI: 10.1111/j.1744-9987.2008.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report on the Role of Plasma Exchange in the Management of a Massive Amlodipine Besylate Intoxication

Abstract: Therapeutic plasma exchange is a procedure used to remove pathologic substances from a patient's blood that has proven useful in some cases of drug overdose. Overdose by calcium channel blocker antihypertensive agents has been shown to be a cause of significant morbidity and can often times prove fatal. These agents cause systemic hypotension by inhibiting cell membrane calcium channels, which leads to a slowing of intracardiac electric conduction with consequent impairment of myocardial function and widesprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…Insulin has been reported to increase serum ionized calcium levels and to improve myocardial carbohydrate utilization and has been suggested in treatment. [11] In addition, although methylene blue (Jang et al [12] ) and plasma exchange [13] have been reported to be beneficial in severe intoxication, it was not necessary in our case. Lipid emulsion was reported to be beneficial in lipophilic drugs intoxications, such as calcium channel blockers in two studies.…”
Section: Discussionmentioning
confidence: 73%
“…Insulin has been reported to increase serum ionized calcium levels and to improve myocardial carbohydrate utilization and has been suggested in treatment. [11] In addition, although methylene blue (Jang et al [12] ) and plasma exchange [13] have been reported to be beneficial in severe intoxication, it was not necessary in our case. Lipid emulsion was reported to be beneficial in lipophilic drugs intoxications, such as calcium channel blockers in two studies.…”
Section: Discussionmentioning
confidence: 73%
“…La sobredosis de calcio antagonista además de la vasodilatación con choque, origina edema pulmonar no cardiogenico por vasodilatación pre capilar; la injuria renal aguda y acidosis metabólica se relacionan con la hipoperfusión, y la disminución en la secreción y la resistencia a la insulina interfieren con el catabolismo de la glucosa incrementando la producción del lactato (5,7,8,10,11).…”
Section: Discussionunclassified
“…Multiple cycles might have limited the duration of the patient's hypoperfusion. 21 Although only a single cycle of plasmapheresis was used, the circulating amlodipine levels measured in this patient suggest that plasmapheresis was a beneficial treatment. Future studies examining the use of plasmapheresis in toxic amlodipine ingestion would better define the role of that treatment.…”
Section: Discussionmentioning
confidence: 99%